The Evolution of Customary Land Law in Negeri Sembilan - Abu Bakar, Noraziah; Md Tah, Ikmal Hisham; Ganti Shaari, Mohd Nazim (Kanun: Jurnal Undang-undang Malaysia, 2025)
Land law in Malaysia is based on the Torrens System, where registration serves as the core principle that grants indisputable ownership rights over the land. Generally, the National Land Code [Act 828] governs the process of land ownership and registration, ensuring that ownership is secure and cannot be challenged by any party. This ownership covers all types of land within state boundaries. Negeri Sembilan, which practises the Adat Perpatih system, is also subject to Act 828. However, Section 4(2) of Act 828 recognises inherited laws that remain relevant to local community. The Adat Perpatih legal system is accepted as a land law still practised in Negeri Sembilan, preserving both its customary legal system and administration of Customary Land. The administration of Customary Land is based on oral law upheld by the Dato’ Lembaga and has also been codified under the Customary Tenure Enactment 1948 (CTE). For transactions involving Customary Land, the CTE provides that approval must be given by the Dato’ Lembaga. However, there is no explicit provision on how this approval is to be given and no clear terms for land development, such as stated in Act 828. When there are no clear provisions related to land development and transaction processes, it becomes difficult for the owners of Customary Land to develop the land and gain benefits from such ownership. Keywords: Registration, indisputable ownership, Adat Perpatih law, transactions, land development Full text:   PDF